Social Stratification - Johnson, Lee A. (Biblical theology bulletin, 2013)
Every society has an organizational structure that reflects what is valued by that society. Those members of the society that are deemed more valuable or that contribute more to society are rewarded with a larger share of the goods and services. The ancient Mediterranean world functioned within a rigid hierarchical structure, in which the most valued members were openly designated—in the family, the city, the empire, and the cosmos. The virtues of the social stratification system were made apparent through the patronage/clientage system as the means of distribution of goods, the cultural battle for honor and the aversion to shame, and the patriarchal structure of the family, to name a few instances. Recognition of the prevailing hierarchical structure in the ancient Mediterranean world sheds light upon biblical writings, some of which affirm, and others of which challenge the cultural customs arising from the hyper-stratification of the societies from which they emerged.